Owned or rented—does it matter? Agricultural land use change within farm properties, case studies from Norway. (November 2015) - Stokstad, Grete; Krøgli, Svein Olav
Highlights: Study of land use changes of agricultural land also within farm properties. Fully cultivated land in the 60 s has kept its land cover class on rented land as on own land. In a marginal region, own or rented land has implications for changes in agricultural areas. Abstract: In Norway and many other countries agriculture has moved toward less, but bigger farms. Total agricultural area has not been much affected mainly due to land tenancy. In this study we used aerial photographs to map land use and land cover in agricultural areas at present and in the mid-sixties. Three study sites were chosen, representing areas of differences with respect to drivers of change and possible differences in their landscape outcome. Maps from the two periods were used to produce transition matrices for the three areas as well as within each farm property. Our main finding on acreage change is that fully cultivated land increases and pastures decreases. A novel feature in our study is that we also include land use changes within single properties. In all three places a large share of the fully cultivated land in the sixties remains fully cultivated land irrespectively of whether the land is in use by its owner or is rented. When we looked at increases of fully cultivated land, the results are mixed. In the less favorable region, ownership to land versus rented land helps explain the variation in gain of fully cultivated land as well as maintained total agricultural area. However, in the case study from the grain region, whether a farm property today is in use as own land or rented, do not help explain the variation in changes within the data sample of farm properties larger than one hectare.